2012
DOI: 10.1682/jrrd.2010.05.0094
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle course: Users maneuverability and movement efficiency when using Otto Bock C-leg, Otto Bock 3R60, and CaTech SNS prosthetic knee joints

Abstract: Abstract-The performance and movement efficiency of prosthesis users while traversing a multisectional obstacle course (OC) were evaluated using a crossover design with random allocation of three prosthetic knee joints: the SNS (CaTech; Dayton, Ohio) the C-Leg (Otto Bock; Duderstadt, Germany), and the 3R60 (Otto Bock). Twelve users completed the OC twice with each joint, once without and once with a mental loading task (MLT). The performance was objectively assessed using time measurement from digital video re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…When subjects used a C-Leg (Ottobock; Duderstadt, Germany) microprocessor prosthetic knee (MPK), they completed the obstacle course more quickly and with fewer steps than when they used nonmicroprocessor knees (NMPKs). Similarly, Meier et al designed a customized obstacle course involving many mobility skills including basic ambulation, stepping up, ramp ascent, turning, and walking across variably resistive surfaces [2]. C-Leg use tended to improve task completion time relative to a hydraulic swing-phase control polycentric knee.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When subjects used a C-Leg (Ottobock; Duderstadt, Germany) microprocessor prosthetic knee (MPK), they completed the obstacle course more quickly and with fewer steps than when they used nonmicroprocessor knees (NMPKs). Similarly, Meier et al designed a customized obstacle course involving many mobility skills including basic ambulation, stepping up, ramp ascent, turning, and walking across variably resistive surfaces [2]. C-Leg use tended to improve task completion time relative to a hydraulic swing-phase control polycentric knee.…”
Section: Introductionmentioning
confidence: 99%
“…Task completion times were not so clearly improved relative to a single axis, fluid-controlled swing and stance knee system. Meier et al found that use of the C-Leg decreased movement efficiency by 10 percent while completing the obstacle course in parallel with a mental loading task [2]. Course completion data regarding time and distance were very fractionalized.…”
Section: Introductionmentioning
confidence: 99%
“…26,27,32,41,170 On performance based measures of mobility, studies reported increased walking speed on both even and uneven terrain, 26 decrease in time that was needed to complete the Timed "up & go" Test, 171 increased performance of ramp and stair de-scent, 27,32,36 and improved obstacle course navigation when walking with a microprocessor-controlled prosthetic knee. 33,35 Finally, studies found no differences in daily step count between prosthetic knee conditions. 27,145 Previous research mainly focused on the C-Leg.…”
Section: Introductionmentioning
confidence: 93%
“…Hafner et al 34 found no differences in walking speed, whereas Meier et al 35 found an increase in walking speed while using a MPK to navigate an obstacle course.…”
Section: Environmental Obstacle Negotiationmentioning
confidence: 99%
See 1 more Smart Citation